A novel fluorescent probe for copper (II) ion based on rare earth polyoxometalate. Issue 10 (26th November 2022) - Li, Na; Chen, Xiaowen; Huang, Yulan; Wang, Li; Li, Jian; Yang, Xiangxiang
Abstract: A new strategy for the determination of Cu(II) ions was developed using K10 H3 [Eu(SiMo6 W5 O39 )2 ]·28H2 O. The polyoxometalate H4 SiMo6 W6 O40 acts as a ligand to sensitize the europium ion to emit red fluorescence, and the fluorescence was quenched by the addition of Cu(II) ions. The luminescence of the central Eu 3+ was quenched due to the inner filter effect (IFE) of Cu(II) to K10 H3 [Eu(SiMo6 W5 O39 )2 ]·28H2 O and the static burst. Therefore, K10 H3 [Eu(SiMo6 W5 O39 )2 ]·28H2 O can be used as a specific fluorescent probe for Cu 2+ and it exhibited a very good linear response range for copper ions from 1 to 20 μM with detection limit of 0.13 µM. The probe was successfully applied to the determination of Cu(II) ions in clam samples with recoveries in the range of 90–98%.